IMPACT OF HUMAN RESOURCE ETIQUETTE ON GUEST SATISFACTION: STUDY RECONNAISSANCE FOR OPINIONS A SAMPLE FROM STAFF IN HOTELS CLASS EXCELLENT IN BAGHDAD - Ola Katran Hassan Fahad ALWawi; DR. Muthanna Alobaidi (Scholar Express Journals, 2023)
The research aims to focus on interest in etiquette, development of human resource skills (HRS) in hotels of research sample, which reflects positively on guest, achieving his satisfaction, directing him towards services of Tourism organization (TO). Where researchers relied on descriptive analytical approach in their study. The sample of study consisted of (300) distributed Baghdad, which are hotels Babylon Rotana Hotel, Baghdad Hotel, Palestine International Hotel, Ishtar International Hotel, Mansour Malia Hotel) with (60) questionnaires. Some statistical means, methods were used that are commensurate with nature of questions prepared in questionnaire, as data was unpacked, analyzed using statistical analysis program (SPSS), as well as arithmetic mean, standard deviation, ratios and frequencies, in order to analyze stability, validity of questionnaire, Cranach's stability coefficient was used. alpha), the five-point Liker scale was adopted in preparation of questionnaire paragraphs, as well as use of (correlation coefficient person) Research concluded that these organizations should be inculcated in hearts of their employees in tourism departments employees (TDE) , taking into account introduction of employees in training courses on etiquette , Art of dealing to gain knowledge of all highend behaviors, which thus contribute to gaining these organizations a good reputation. Aim to search to focus on interest by etiquette ( HRS) in Hotels a sample search, command that reflected in affirmative on guest , achieve satisfaction he have, direct it Toward services (OT). Where I depend two researchers on curriculum descriptive Analytical in their studies. formed a sample study from (300) Done distributed on number from hotels a sample search in city Baghdad Which Hotels (hotel Babylon Rotan, hotel Baghdad, hotel Palestine international, hotel Ishtar international, hotel Mansour carefully) And in reality (60) resolution. He has It was completed Use some means , styles statistic that fit with nature questions stomach in Form questionnaire, so It was completed vacuation data, analyzed using program analysis statistic (SPSS), as well middle Arithmetic , deviation normative And lineage, iterations, for analysis stability Resolution , believe her It was completed Use ( Factor stability Cranach's alpha)as It was completed Approval Scale Likert quintet in Preparation vertebrae resolution, as Use(Factor Engagement link Correlation coefficient person)And he concluded search to that This is amazing organizations He should that inculcate in souls its employees in sections tourist employees, Enter employees in courses training on etiquette , art deal to earn Knowledge which contribute Subsequently gain, conclusions , recommendations. Tourist, hotel organizations seek to direct towards the guest, by providing the best services to him during his stay in hotel or during participation in organized tourist (OT) trip program, to meet their various needs, to gentle, tactful treatment
Keywords: Development of human resource; Toward services; Tourism Departments Employees